Optimalisasi Artifial Intellegence (AI) dalam Penyusunan Media Ajar Guru Sekolah Dasar di Kabupaten Kendal - Kartinah, Kartinah; Huda, Choirul; Prasetyowati, Dina; Damayani, Aries Tika (LOSARI DIGITAL, 2025)
Producing quality graduates is one of the goals of learning in schools. Therefore, to get the quality of graduates, it is necessary to improve the quality of learning in schools continuously. One way to improve the quality of learning in the classroom is to improve teacher competence. One of the teacher competencies that need to be improved in relation to learning in the classroom is creating learning using creative and innovative learning media. This community service aims to optimize the use of Artificial Intelligence (AI) technology in preparing teaching media for elementary school teachers in Kendal Regency. The lack of ability of elementary school teachers in Kendal Regency, especially at State Elementary School 1 Patukangan in using learning media, makes teachers need to be equipped with knowledge and skills in making learning media. The methods used in this activity include preparation, training, mentoring and evaluation stages. The results obtained from this PKM activity are 90% of elementary school teachers in Kendal district who take part in the workshop have been able to develop learning media that can be used in classroom learning especially related to multimedia with materials that support the development of Artificial Intelligence-based teaching materials.